2021
DOI: 10.1002/casp.2532
|View full text |Cite
|
Sign up to set email alerts
|

Lost in transition: What refugee post‐migration experiences tell us about processes of social identity change

Abstract: This paper presents findings based on over 40 hrs of rich, phenomenological narrative interview data in which five Syrian refugees describe their experiences of transitioning to a new life in Brazil. Using the Social Identity Model of Identity Change (SIMIC) as a framework for examining the relationship between a period of vulnerability, multiple social identities and wellbeing, interviews were combined with a “talking stones” technique. Key themes of identity “recovery” and “discovery” were consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although including ethnicity and socio-economic status as covariates did not alter the findings of the present research, future research should investigate how different stigmatised categories experience loneliness and transition processes. Mixed methods research may be particularly useful in this regard to help disentangle some of the nuance and complexities surrounding life transitions and loneliness (Ballentyne, Drury, Barrett, & Marsden, 2021; Ng, Haslam, & Haslam, 2018; Seppälä, Riikonen, Paajanen, Stevenson, & Finell, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although including ethnicity and socio-economic status as covariates did not alter the findings of the present research, future research should investigate how different stigmatised categories experience loneliness and transition processes. Mixed methods research may be particularly useful in this regard to help disentangle some of the nuance and complexities surrounding life transitions and loneliness (Ballentyne, Drury, Barrett, & Marsden, 2021; Ng, Haslam, & Haslam, 2018; Seppälä, Riikonen, Paajanen, Stevenson, & Finell, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These challenges may impede an individual's sense of belonging and overall well-being. Another potential challenge brought on by migration is a change in identity as the individual seeks to adapt to new social and cultural experiences (Ballentyne et al, 2020) and struggles to find a balance between previous and current ways of living, including new social roles. Berry and colleagues (1987) have argued that although the transition to a new setting is stressful, acculturative stress varies widely between groups and individuals and does not necessarily lead to negative mental health outcomes.…”
Section: Acculturative Stressmentioning
confidence: 99%
“…Participants often referred to social group membership when characterizing the stranger (e.g., children, black people). According to the Social Identity Model of Identity Change (SIMIC; Haslam et al, 2021), social group membership becomes more salient when people face life-changing events (e.g., (forced) migration, natural disasters, human rights violations; Ballentyne et al, 2021;Greenaway et al, 2015). Research has shown that people going through life changes often develop (new) social group memberships (e.g., survivors' groups, patients' associations) that help them to face and cope with the situation through a sense of community and shared experience (Greenaway et al, 2016).…”
Section: What Kind Of Suffering Do People Engage With?mentioning
confidence: 99%